Regula Pastoralis of Gregory the Great: Respecting the Poor and the Rich with Humanity - Tinambunan, Edison R.L.; Yan Olla, Paulinus (Seri Filsafat Teologi, 2024)
This paper focuses on the consolation of the poor and the rich, as taken from Gregory the Great' book, Regula Pastoralis. This research is based on the ancient writings of the figure; therefore, the applicable methodology is qualitative with the approach of analysis and synthesis to find the dimensions of consolation for the poor and the rich. The research aims to make humanity a consolation for both statuses of life. Although both are very sensitive, especially in Indonesia, but being aware of human values becomes a means of consolation. Rich people can become poor and poor people can become rich, but humanity will never change its value. Therefore, upholding humanity is a way to uplift the dignity of the rich and the poor.